THE ROLE OF VASCULAR GROWTH FACTORS IN DIABETIC RETINOPATHY AND MACULAR EDEMA DEVELOPMENT - A. G. Iskhakova; A. V. Zolotarev; D. A. Viktorov; A. N. Toropovsky; A. G. Nikitin (Российский офтальмологический журнал, 2018)
The paper discusses the key role of VEGF and PlGF in the pathogenesis of diabetic retinopathy and macular edema and describes the mechanisms of retinal neoangiogenesis under the influence of these factors. An overview of treatment methods of retinopathy and macular edema is given, with a focus on anti-VEGF therapy. Anti-VEGF drugs are listed and compared, taking account of the results of their clinical trials. For citation: Iskhakova A.G., Zolotarev A.V., Viktorov D.A., Toropovsky A.N., Nikitin A.G. The role of vascular growth factors in diabetic retinopathy and macular edema development. Russian ophthalmological journal. 2018; 11 (2): 62-9. doi: 10.21516/2072-0076-2018-11-2-62-69 (In Russian).